Etiopathological investigations on clinical dropsy in carps (Cyprinus carpio) due to Aeromonas hydrophila in Himachal Pradesh - PATHANIA, DEEPAK; KATOCH, R C; MAHAJAN, ARVIND; SHARMA, MANDEEP; PAUL, RAJENDER (The Indian Journal of Animal Sciences, 2014)
Carps (Cyprinus carpio) exhibiting clinical symptoms of abdominal dropsy were collected from Gobind Sagar reservoir and Government Carp Breeding Farm, Ghagus, for etiopathological investigations. The representative morbid materials were processed microbiologically so as to ascertain the etiology of abdominal dropsy among carps. On gross examination the affected fish discerned excessive haemorrhages on the body surface and perceptible abdominal distention. Postmortem findings revealed hyperaemia of viscera, petechial to ecchymotic haemorrhages over mesentry, parietal peritoneum and sanguinous ascitic fluid. Histopathological changes included focal necrosis and severe oedema in the liver, with a marked chordal disarray and necrosis of renal tubules in the kidney. An excessive haemosiderin pigment accumulation was discerned in the liver parenchyma and kidney. Motile aeromonads as Aeromonas hydrophila spp. hydrophila were isolated in pure cultures from the pooled visceral organs, kidneys and abdominal exudates. The organism was found most sensitive to gentamicin.